Comparison of two methods of making reduced-fat ovine Halloumi type cheese - KAMINARIDES, S. (Journal of the Hellenic Veterinary Medical Society, 2018)
Halloumi is a popular cheese in Cyprus where reduced-fat Halloumi cheese is manufactured solely from bovine milk. In this study, two methods of making reduced-fat Halloumi type cheeses from ovine milk containing 1.8% fat were compared. Ovine milk was used because it has a greater biological and nutritional value than bovine milk. The first method used traditional technology (T) as a control whereas the second method was a modified technology (M), as described in material and methods. The M cheese had a significantly (P<0.05) higher yield, moisture content, protein in dry matter, pH value and lower content of fat, lactose, ash, Ca and Mg, acidity, hardness, adhesiveness, elasticity, gumminess and chewiness than the T cheese. The assessment panel suggested that the M technology was superior and can be used to produce a reduced-fat ovine Halloumi type cheese.